2019
DOI: 10.1007/s11238-019-09707-6
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation and modelling of imprecise utility of health states

Abstract: Utilities of health states are often estimated to support public decisions in health care. People's preferences may be imprecise, for lack of actual trade-off experience. We show how to elicit the utilities accounting for imprecision (using fuzzy sets), discover the main drivers of imprecision, and compare several approaches to modelling health state utility data in the fuzzy setting. We extended the time trade-off (TTO) questionnaire, to elicit utilities of states defined in the EQ-5D-3L descriptive system (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The mixed-method convergent approach that we followed in this secondary analysis provided a deeper understanding of individual preferences on thromboprophylaxis in pregnancy. While value elicitation exercises (scoring health states) are well accepted(48, 49), they can, in some instances, be imprecise for people's lack of trade-off experience (50). Furthermore, some authors (32) argue that health states valuations are likely to be a function of both the severity of the health state and the context of the choice; for example, responses to standard gamble questions are likely to be in uenced by attitudes toward risk.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The mixed-method convergent approach that we followed in this secondary analysis provided a deeper understanding of individual preferences on thromboprophylaxis in pregnancy. While value elicitation exercises (scoring health states) are well accepted(48, 49), they can, in some instances, be imprecise for people's lack of trade-off experience (50). Furthermore, some authors (32) argue that health states valuations are likely to be a function of both the severity of the health state and the context of the choice; for example, responses to standard gamble questions are likely to be in uenced by attitudes toward risk.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The health state valuation literature since MVH 8 and Dolan 1 to Viney et al 9,11 has operationalized perceived implausible states in terms of two-way contrasting combinations (also see Jakubczyk and Golicki, 12 Lim et al, 27 or Bagust 28 ). However, there are 3 things to note.…”
Section: Why Use General Population Data Sets For Stage 1?mentioning
confidence: 99%
“…However, as the authors state, the exercise examined only the efficiency of designs and not the measurement error attributable to the difficulty of imagining these states. In a separate study, Jakubczyk and Golicki 12 applied an experimental TTO design to examine the amount of imprecision around health preferences from a Polish student sample. The authors found that values of states with two-way contrasting combinations have higher imprecision and that imprecision is mostly driven by UA and AD.…”
mentioning
confidence: 99%